2017
DOI: 10.3390/ph10040086
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils and Antifungal Activity

Abstract: Since ancient times, folk medicine and agro-food science have benefitted from the use of plant derivatives, such as essential oils, to combat different diseases, as well as to preserve food. In Nature, essential oils play a fundamental role in protecting the plant from biotic and abiotic attacks to which it may be subjected. Many researchers have analyzed in detail the modes of action of essential oils and most of their components. The purpose of this brief review is to describe the properties of essential oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
384
0
19

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 506 publications
(411 citation statements)
references
References 138 publications
(155 reference statements)
8
384
0
19
Order By: Relevance
“…; Nazzaro et al . ). Previous studies showed that various natural plant extracts are believed to have antifungal property and many essential oils have been reported to have antifungal activities, such as Syzygium aromaticum against Alternaria alternata (Costa et al .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…; Nazzaro et al . ). Previous studies showed that various natural plant extracts are believed to have antifungal property and many essential oils have been reported to have antifungal activities, such as Syzygium aromaticum against Alternaria alternata (Costa et al .…”
Section: Introductionmentioning
confidence: 97%
“…Essential oils are considered as alternative biological control compounds due to their inhibitory activity on pathogen growth either as main components or as antimicrobial adjuvants (Abdel-Kader et al 2011;Nazzaro et al 2017). Previous studies showed that various natural plant extracts are believed to have antifungal property and many essential oils have been reported to have antifungal activities, such as Syzygium aromaticum against Letters in Applied Microbiology 67, 400--410 © 2018 The Society for Applied Microbiology Alternaria alternata (Costa et al 2011); Cymbopogon citratus and Ocimum basilicum against Phytophthora species (Amini et al 2016); and Mentha piperita and Pelargonium roseum against Lecanicilium fungicola (Mehrparvar et al 2016), among others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, some EOs may inhibit the action of some enzymes, including mitochondrial enzymes such as lactate, malate, and succinate dehydrogenases. These enzymes are involved in ATP biosynthesis (Chen et al 2013; Nazzaro et al 2017) as well as H + -ATPase activity; inhibiting these processes leads to intracellular acidification and cell death (Ahmad et al 2013). The inhibition of mycelial growth also depends on the concentration of EOs (Dambolena et al 2010; Gömöri et al 2013; Sumalan et al 2013; Kumar et al 2014; Elgorban et al 2015; Perczak et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This direct antimicrobial or antifungal activity of EOs might mainly be caused by the properties of their terpenes/terpenoids, that—due to their highly lipophilic nature and low molecular weight—are capable of disrupting the cell membrane, causing cell death or inhibiting the sporulation and germination of fungi (42). Antifungal properties are generally linked to cell membrane disruption, alteration and inhibition of cell wall formation, dysfunction of the fungal mitochondria, inhibition of efflux pumps and / or ROS production.…”
Section: Resultsmentioning
confidence: 99%